Reboot leadership and the art of growing up - Colonna, Jerry (New York HarperBusiness, 2019)
Jerry Colonna helps start-up CEOs make peace with their demons, the psychological habits and behavioral patterns that have helped them to succeed?molding them into highly accomplished individuals?yet have been detrimental to their relationships and ultimate well-being. Now, this venture capitalist turned executive coach shares his unusual yet highly effective blend of Buddhism, Jungian therapy, and entrepreneurial straight talk to help leaders overcome their own psychological traumas. Reboot is a journey of radical self-inquiry, helping you to reset your life by sorting through the emotional baggage that is holding you back professionally, and even more important, in your relationships.
Keywords: Leadership